Odanacatib increases mineralized callus during fracture healing in a rabbit ulnar osteotomy model. Issue 1 (7th August 2015) - Pennypacker, Brenda L.; Gilberto, David; Gatto, Nicholas T.; Samadfam, Rana; Smith, Susan Y.; Kimmel, Donald B.; Thi Duong, Le
ABSTRACT: The effects of the cathepsin K inhibitor odanacatib (ODN) on fracture healing were monitored for ∼6 and 15 weeks post‐fracture in two separate studies using the unilateral transverse mid‐ulnar osteotomy model in skeletally mature female rabbits. Rabbits were pre‐treated for 3–4 weeks with vehicle (Veh), ODN (2 mg/kg, po, daily), or alendronate (ALN) (0.3 mg/kg, sc, twice‐weekly) prior to osteotomy. In Study 1, the animals were maintained on the same respective treatment for ∼6 weeks. In Study 2, the animals were also continued on the same therapy or switched from Veh to ODN or ODN to Veh for 15 weeks. No treatment‐related impairment of fracture union was seen by qualitative histological assessments in the first study. Cartilage retention was detected in the calluses of ALN‐treated rabbits at week‐6, while calluses in the ODN and Veh groups contained bony tissue with significantly less residual cartilage. ODN treatment also markedly increased the number of cathepsin K‐(+) osteoclasts in the callus, indicating enhanced callus remodeling. From the second study, ex vivo DXA and pQCT confirmed that ODN treatment pre‐ and post‐osteotomy increased callus bone mineral content and bone mineral density (BMD) versus Veh ( p < 0.001) and discontinuation of ODN post‐surgery returned callus BMD to Veh. Peak load of ODN‐ or ALN‐treated calluses were comparable to Veh. ODN increased callus yield load (20%, p = 0.056) and stiffness (26%, p < 0.05) versus Veh. These studies demonstrated that ODN increased mineralized callus during the early phase of fracture repair without impairing callus formation or biomechanical integrity at the fracture site. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:72–80, 2016.